Combined electrokinetic manipulations of pathogenic bacterial samples in low-cost fabricated dielectrophoretic devices - Martínez Brenes, Alejandro (2019)
A low-cost fabrication method of microfluidic devices with micrometer-sized constrictions used for electrodeless dielectrophoresis (eDEP) is demonstrated here. A structure on a commercial printed circuit board (PCB) template of one-sided copper clad fiberglass-epoxy laminate was used as a molding master for polydimethylsiloxane (PDMS) soft lithography. This was achieved by printing a constriction-based microchannel pattern on glossy paper with a micrometer-scaled resolution laser printer and transferring it to the laminate’s Cu face, rendering a microstructure of ∼17 µm height and various widths across tips. The Cu master’s pattern was transferred to PDMS, and smooth constrictions were observed under the microscope. Following air plasma encapsulation, PDMS chips were loaded with an inactivated bacterial sample of fluorescently stained Brucella abortus vaccine strain S-19 and connected to an amplified voltage source to examine the sample’s response to electric field variations. After an AC/DC electric field was applied to the bacterial solution in the microfluidic device, the combined effect of electrokinetic + hydrodynamic mechanisms that interact near the dielectric microconstrictions and exert forces to the sample was observed and later confirmed by COMSOL simulations. Our fabrication method is an alternative to be used when there is no access to advanced microfabrication facilities and opens ways for target selection and preconcentration of intracellular pathogens as well as sample preparation for metagenomics.